2011
DOI: 10.5392/jkca.2011.11.10.324
|View full text |Cite
|
Sign up to set email alerts
|

Relations among the Decision Making Style, Self Leadership and Communication Competence of Visiting Nurses

Abstract: The aim of this study was to explore relations among the decision making style, self leadership and communication competence of visiting nurses. The research design was a descriptive survey study, and 219 people were selected through convenience sampling among the visiting nurses who worked in the 28 community based health care centers. The most frequent decision making style of visiting nurses was a rational style. The scores of self leadership and communication competence of visiting nurses were also showed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…Marital status 8 (30.8) Im (2012), Jung (2012), Min et al (2011), Kang et al (2010), Kang et al (2009), Lee (2007), Kim (2007), Kim & Kwak (2006) Married status revealed higher S-L than single Position 8 (30.8) Im (2012), Min et al (2011), Min et al (2009), Kang et al (2009), Kim (2009), Lee (2007), Kim (2007), Park (2007) Head nurse revealed higher S-L than clinical nurse Kang et al (2009), Kim (2009), , Lee (2007), Kim (2007), Park (2007), Seomun et al (2006), Cho (2003) Long career revealed higher S-L 1 (3.8) Seo (2012) Less than 1 year revealed higher S-L than 2-3 years No difference 1 (3.8) Kim & Hong (2007) No comments 7 (26.9) Lee (2012), Hong (2011), Im (2011), Kim et al (2011), , , Park (2009) S-L=self-leadership. 2010, Kang et al (2010), Kang et al (2009), , Lee (2007), Kim & Hong (2007), Seomun (2005), Cho (2003) Higher S-L, higher job satisfaction Job stress 2 (7.7) , Kim & Hong (2007) Higher S-L, lower job stress (negative correlation)…”
Section: 셀프리더십 측정도구mentioning
confidence: 99%
“…Marital status 8 (30.8) Im (2012), Jung (2012), Min et al (2011), Kang et al (2010), Kang et al (2009), Lee (2007), Kim (2007), Kim & Kwak (2006) Married status revealed higher S-L than single Position 8 (30.8) Im (2012), Min et al (2011), Min et al (2009), Kang et al (2009), Kim (2009), Lee (2007), Kim (2007), Park (2007) Head nurse revealed higher S-L than clinical nurse Kang et al (2009), Kim (2009), , Lee (2007), Kim (2007), Park (2007), Seomun et al (2006), Cho (2003) Long career revealed higher S-L 1 (3.8) Seo (2012) Less than 1 year revealed higher S-L than 2-3 years No difference 1 (3.8) Kim & Hong (2007) No comments 7 (26.9) Lee (2012), Hong (2011), Im (2011), Kim et al (2011), , , Park (2009) S-L=self-leadership. 2010, Kang et al (2010), Kang et al (2009), , Lee (2007), Kim & Hong (2007), Seomun (2005), Cho (2003) Higher S-L, higher job satisfaction Job stress 2 (7.7) , Kim & Hong (2007) Higher S-L, lower job stress (negative correlation)…”
Section: 셀프리더십 측정도구mentioning
confidence: 99%